Biyoistatistiğin Gelişimi: Geçmişten Geleceğe - A. Ergun Karaağaoğlu; Sevilay Karahan (Düzce Tıp Fakültesi Dergisi, 2021)
Biostatistics which is the application of statistics in the field of health and biology; provides powerful tools for creating questions, designing studies, developing measurements, and analyzing data and has an important place in determining the efficacy and safety of products such as drugs and vaccines. The impact of statistical sciences on medical and biological sciences has increased rapidly during the last few decades. Clinicians need to understand statistics well enough to follow up and evaluate empirical studies that provide an evidence base for clinical practice. Recent advances in biomedical research have created both new challenges and opportunities for statisticians and data scientists. Big data analytics, precision medicine, artificial intelligence, causal inference, and other new research resources inspire data scientists to develop modern statistical methods and innovative inference procedures. Therefore new philosophies such as causal models and prediction, new models such as graphical chain models and random effects models, faster computers and new clever algorithms for integration and maximization are needed. Without adequate investment in biostatistics, all medical research is at a significant risk of “drowning in data, but starving for knowledge”.